Network Pharmacology to Reveal the Mechanism of Fufang Banmao Capsule for Treating Unresectable Primary Liver Cancer and Clinical Data Validation - Hu, Youwen; Xiao, Yangyang; Wan, Lijun; Wen, Zhili (Current Pharmaceutical Design, 2024)
IntroductionFufang Banmao capsule (FFBM), a traditional Chinese medicine, has been used to treat primary liver cancer (PLC) for several years. However, the bioactive ingredients, and mechanism of FFBM for treating PLC remains unclear. Our objective is to utilize network pharmacology to investigate these aspects and subsequently validate their effectiveness through clinical data.Materials and MethodsThe FFBM ingredients were obtained from the HERB database and screened for bioactive ingredients using the SwissTargetPrediction database. The PharmMapper and GEO database were used to acquire targets and differentially expressed genes (DEGs) for FFBM and PLC, respectively. Common targets were identified using Venn diagrams, followed by enrichment and protein-protein interaction (PPI) analysis. Furthermore, the Cytoscape software was utilized to identify Hub genes and construct the ingredient- target-pathway network. Subsequently, patients diagnosed with unresectable PLC who underwent transcatheter arterial chemoembolization (TACE) at our hospital between January 2008 and December 2019 were retrospectively collected. Finally, Cox analysis was conducted to reveal the role of FFBM in the treatment of unresectable PLC.ResultsFFBM had 232 targets, and PLC had 1582 DEGs. HSP90AA1 and SRC were identified as crucial targets. Alpha-santalol, glycyrrhizin, and morroniside were identified as the top three bioactive ingredients. Enrichment analysis revealed a significant connection between FFBM utilization for treating PLC and multiple pathways, such as chemical carcinogenesis, PI3K-AKT, Rap1, FoxO, MAPK, and VEGF pathway. Clinical data revealed that consuming FFBM significantly improved the prognosis of unresectable PLC with a hazard ratio of 0.69.ConclusionOur study identified the bioactive ingredients of FFBM and its potential mechanisms for treating PLC. Additionally, we validated the effectiveness through clinical data.
Keywords: clinical research